2019
DOI: 10.3390/cryst10010014
|View full text |Cite
|
Sign up to set email alerts
|

Three Multi-Components Reaction: Synthesis and X-Ray Single-Crystal of Hydroacridinone-Based Hydrazino-S-Triazine Derivative as a New Class of Urease Inhibitor

Abstract: The one-pot fashion of three multi-component reaction provides the desired hydroacridinone-based hydrazino-s-triazine scaffold 4. Compound 4 was crystallized in an orthorhombic crystal system and Pbca space group with a = 11.6271(2) Å, b = 18.2018(4) Å, c = 32.4721(6) Å, and α = β = γ = 90° with one formula unit per asymmetric unit and eight molecules per unit cell. Additionally, structural features, Hirshfeld surfaces, and DFT studies were also investigated. Its packing in the crystal is controlled by H…H (63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…The central fragment of the molecule is almost planar, the mean deviations of C(2) and C(7) atoms are 0.60 and 0.77 Å, respectively. The redistribution of bond lengths and bond angles in the central fragment correlates well with those of substituted 1,2,3,4,5,6,7,8‐octahydro acridine [9,10,16–19] and 1,8‐acridinones [20–24] reported previously. The H(14) atom is involved in an intramolecular C‐H…N contact to form a planar five‐membered ring (N…H(14)=2.376 Å, NH(14)C(14)=106.5°).…”
Section: Resultssupporting
confidence: 84%
“…The central fragment of the molecule is almost planar, the mean deviations of C(2) and C(7) atoms are 0.60 and 0.77 Å, respectively. The redistribution of bond lengths and bond angles in the central fragment correlates well with those of substituted 1,2,3,4,5,6,7,8‐octahydro acridine [9,10,16–19] and 1,8‐acridinones [20–24] reported previously. The H(14) atom is involved in an intramolecular C‐H…N contact to form a planar five‐membered ring (N…H(14)=2.376 Å, NH(14)C(14)=106.5°).…”
Section: Resultssupporting
confidence: 84%
“…Recently, several classes of compounds including hydroxamic acids, [16,17] phosphoramidites, [18] boronic and boric acids, [19] quinones, [20,21] heavy metal ions, [22] imidazoles, [23] and others have been investigated as urease inhibitors [24–30] . The bacterial ureases can also be inhibited by the five‐membered heterocycles like 1,2,4 triazoles and 1,3,4 oxadiazoles [30–35] .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, several classes of compounds including hydroxamic acids, [16,17] phosphoramidites, [18] boronic and boric acids, [19] quinones, [20,21] heavy metal ions, [22] imidazoles, [23] and others have been investigated as urease inhibitors. [24][25][26][27][28][29][30] The bacterial ureases can also be inhibited by the five-membered heterocycles like 1,2,4 triazoles and 1,3,4 oxadiazoles. [30][31][32][33][34][35] It is documented that some of the 1,3,4 oxadiazoles derived Mannich bases decrease inflammation and prevent fungal growth and they also possess analgesic, antiulcer, antibacterial, anti-HIV, anti-convulsant, anti-tuberculosis and anticancer activities and as inhibitors of various other enzymes and are used in many other applications.…”
Section: Introductionmentioning
confidence: 99%
“…These examples also reveal a range of applications. [16][17][18] For example, El-Faham et al designed and synthesized a variety of s-triazine hybrids with mono-/dipyrazolyl and piperidine moieties, which were then tested for cancer activity and toxicity in vivo. 19 Matthew A. Sanders et al have reported tri-substituted s-triazine as new lead compound TZ9 for selective RAD6B inhibitory activity and cellular anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%